The Effectiveness Of Online Services At The Population And Civil Registration Services Of Pekanbaru City - Abid Arrijal; Dadang Mashur (Pencerah Publishing, 2021)
Online service is one of the service procedures carried out by the Pekanbaru City Population and Civil Registry Service in serving the needs of the community when they want to take care of population administration which was formed based on the decision of the Head of Service Number 208 of 2019, namely regarding the formation of public service innovations in the form of a Sipenduduk website and the decision of the head of service number 43 of 2020 concerning the formation of public service innovations in the LAGU application. To realize an effective public service process, a service process that is fast, easy, cheap, and straightforward is required. However, in the process of running this online service, there are still several factors that become obstacles in an effort to realize effective services, namely the lack of awareness of dukcapil services to the needs of the people of Pekanbaru City who take care of population administration. , lack of readiness of facilities and infrastructure as well as human resources owned by the Agency, and socialization of online services to less active people. This study aims to determine the effectiveness of online services carried out by the Department of Population and Civil Registration of Pekanbaru City. The theoretical concept that the researcher uses is the theory of effectiveness according to Mahmudi 2019. By using qualitative research methods and data collection techniques based on interviews, observation and documentation. The results of the research that the author can, namely the implementation of online services, there are still several factors that become obstacles experienced by the Department of Population and Civil Registration of Pekanabaru City, so that online services implemented have not been effective